Strategic planning in university athletic departments in the United Kingdom - Kriemadis, T. (The Sport Journal, 2009)
The study`s purposes were to (a) determine the extent to which university athletic departments in the United Kingdom use strategic planning, (b) identify key factors discouraging strategic planning, and (c) examine relationships between use of strategic planning and the variables university size and athletic director`s background. Of athletic departments studied, 59.5% were strategic planners that wrote long-range plans, assessed external and internal environments, and based strategies on department mission and objectives. The remaining 40.5% were nonstrategic planners using just some components of the strategic planning process, as either users of short-range written plans and budgets, for the current fiscal period; users of unwritten short-range plans maintained in an administrator`s memory (intuitive planners); or users of no measurable planning procedures.